PENGARUH DUKUNGAN SOSIAL DAN RESILIENSI TERHADAP KUALITAS HIDUP SUBJEKTIF NELAYAN YANG TERDAFTAR DALAM DATA PENSASARAN PERCEPATAN PENGHAPUSAN KEMISKINAN EKSTRIM (P3KE) DI KABUPATEN PANGANDARAN - Primantika, Dwi Wiwin; Adi, Isbandi Rukminto (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
This study aims to see the effect of social support and resilience on fishermen's subjective quality of life in Pangandaran Regency. The measurements used to measure fishermen's subjective quality of life include aspects of physical well-being, social well-being, material well-being, development and activity, and emotional well-being. This study uses a quantitative method with survey data collection techniques. The data analysis technique used was the Somers correlation technique which was analyzed through SPSS (Statistical Package for Social Sciences). Data were collected by survey using three instruments from the subjective quality of life variables, social support, and resilience, with 243 fishermen who were heads of families. The results of this discovery revealed that social support has a positive and significant relationship with the subjective quality of life of fishermen, with a p-value of 0.00 and a correlation coefficient of 0.462 (moderate), and the resilience variable has a positive and significant influence on the subjective quality of life of fishermen with a p-value of 0.00 and a correlation coefficient of 0.520 (moderate). Keywords: Social Support, Resilience, Subjective Quality of Life, Fisherman